Gambaran Karakteristik dan Faktor Risiko Terjadinya Speech Delay pada Anak di Klinik Tanaya pada Tahun 2023 - Zahra Noerjanah Usmany; Herri S. Sastramihardja; Miranti Kania Dewi (Bandung Conference Series: Medical Science, 2024)
Abstract. Symptoms of speech delay are a common developmental disorder that occurs in around 5% - 8% of the child population. The prevalence of speech delays in children aged 2-7 years in the United States ranged from 2.3-19% in 2018. The aim of this study was to determine the characteristics and risk factors for speech delays in children at the Tanaya Clinic in 2023. Research methods This is a descriptive quantitative observational design using a cross sectional study to obtain an overview of characteristics and risk factors. Sampling was taken using a non-probability sampling technique with a convenience sampling method. The research results that met the inclusion criteria were 13 people. The results of research on the description of the characteristics of children with speech delay, there is a tendency for speech delay in children aged 3-6 years, the dominant gender is 10 boys. There are internal risk factors such as a history of term birth. A total of 9 children were born not premature (> 37 weeks). External Risk Factors in Children with Speech Delay at the Tanaya Clinic with the duration of exposure to gadgets for 9 children more than two hours. Family-based risk factors, dominantly experiencing father absence, were 6 people. In conclusion, description of the characteristics and risk factors that will most often occur during 2023 in children with speech delay, most often are children aged 3-6 years, male, exposure to gadgets for more than two hour. Based on the research results, it is hoped that it can become a reference for other research to deepen the description of characteristics and other risk factors using a larger number of respondents and using other methods. Abstrak. Gejala keterlambatan bicara (speech delay) merupakan gangguan perkembangan yang umum terjadi pada sekitar 5% - 8% populasi anak. Prevalensi keterlambatan bicara pada anak usia 2-7 tahun di Amerika Serikat berkisar antara 2,3-19% pada tahun 2018. Tujuan pada penelitian ini adalah mengetahui gambaran karakteristik dan faktor resiko terjadinya speech delay pada anak di Klinik Tanaya pada tahun 2023. Metode penelitian ini adalah dengan desain observasional kuantitatif deskriptif menggunakan studi cross sectional untuk mendapatkan gambaran karakteristik dan faktor resiko. Pengambilan sampel diambil melalui Teknik non-probability sampling dengan metode convenience sampling. Hasil penelitian yang memenuhi kriteria inklusi sebanyak 13 orang. Hasil penelitian pada gambaran karakteristik pada anak dengan speech delay, Ada kecenderungan speech delay pada anak-anak usia 3-6 tahun, dominan berjenis kelamin laki-laki 10 orang. Terdapat faktor risiko internal seperti riwayat kelahiran cukup bulan, Sebanyak 9 anak lahir tidak prematur (> 37 minggu). Faktor Risiko Eksternal pada Anak dengan Speech Delay di Klinik Tanaya dengan durasi paparan gadget sebanyak 9 anak lebih dari dua jam. Faktor risiko berbasis keluarga, dominan mengalami ketidakhadiran ayah sebanyak 6 orang. Simpulan, gambaran karakteristik dan faktor resioko yang paling banyak terjadi selama tahun 2023 pada anak dengan speech delay, paling banyak adalah anak-anak usia 3-6 tahun, berjenis kelamin laki-laki, paparan gadget lebih dari dua jam. Berdasarkan hasil penelitian diharapkan dapat menjadi acuan untuk penelitian lain memperdalam gambaran karakteristik dan faktor resiko lainnya menggunakan responden yang lebih besar dan menggunakan metode lain.